Historiography of Empathy: Contributions to Social Work Research and Practice - Watson, Tracy; Hodgson, David; Watts, Lynelle; Waters, Rebecca (SAGE, 2021)
Empathy has long been considered critical to good social work practice, and is supported by extensive research and literature. However, empathy is a contested concept with divergent theoretical origins that complicates its place in social work research and practice. This article provides a historical review of empathy, highlighting the evolution of the concept of empathy, its contested history, and subsequent emergence into therapeutic contexts, particularly within social work. Findings show that empathy has multiple definitions and meanings, thus, creating a challenge to research efforts and social work activities. This review lays the groundwork for further constructive debate and research into the theory and practice of empathy for social work.